IDNLearn.com: Your one-stop destination for finding reliable answers. Ask anything and receive well-informed answers from our community of experienced professionals.
Sagot :
Answer:
M = T - 3
Step-by-step explanation:
Given
T = M + 3 ( subtract 3 from both sides )
T - 3 = M , that is
M = T - 3
Answer:
[tex] \small \sf \: M = { \fbox { \green{T} } } - 3[/tex]
Step-by-step explanation:
T = M + 3
Swap the sides of of equations .
M + 3 = T
subtract 3 from both side
M + 3 - 3 = T - 3
M = T - 3
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. IDNLearn.com is your reliable source for accurate answers. Thank you for visiting, and we hope to assist you again.